Evaluación y calidad educativa. Planes y programas para la evaluación de centros en Castilla y León - Jordán, José Manuel (Avances en Supervisión Educativa, 2023)
The evaluation of the educational centres in Castilla y Leon region is a strategic process associated with the quality concept. It searches for information that allows to improve the processes in the educational centres themselves and in the general system. It takes place since the beginning of the decentralization of competences in the field of education, year 2000, and it has meant generating strategies and instruments that allows effectiveness and efficiency both in external evaluation and self-assessment. The new development lines would walk towards the excellence as a new context to adapt environmental demands and the objectives of the education system itself. The role of the inspection in this environment is basic, as it allows to actively participate in the knowledge of the educational centres, in the advice to their processes, and in the decision making of the new lines of work